The relationship between athletes’ music in mood regulation and positive psychological capital and athletic performance - Choi, Young-Jun; Kim, Han-Byul; Kim, Kyungjin (Frontiers in Psychology, 2025)
IntroductionThis study explores the connection between athletes’ use of music in mood regulation, positive psychological capital, and athletic performance. While music is widely acknowledged for its psychological benefits, its role in enhancing athletes’ posi-tive psychological capital and influencing performance outcomes remains insufficiently understood.MethodsA survey was conducted with 417 athletes, and the collected data were ana-lyzed using descriptive statistics, confirmatory factor analysis (CFA), correlation analysis, and structural equation modeling (SEM) to examine the research content.ResultsThe results showed that, first, athletes’ use of music for mood regulation had a positive effect on the positive psychological capital. Second, athletes’ use of music for mood regulation did not have a statistically significant effect on athletic performance. Third, the positive psychological capital of athletes had a positive effect on the athletic performance.DiscussionIt is necessary to provide education and strategies that help athletes regulate their mood using music. Further, the research on the effects of music in mood regulation, which can be expected to positively affect athletes’ positive psychological capital and athletic performance, should be expanded.